CENTRAL OR PERIPHERAL INJECTION OF A FORMULATION CONTAINING THE ANGIOTENSINERGIC DIPEPTIDE ASP-ARG REDUCES ARTERIAL PRESSURE AND CARDIAC INOTROPY IN HYPERTENSIVE RATS - Mendonca, Michelle (2024)
Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP)